AB0363 Traditional Cardiovascular Risk Factors in Rheumatoid Arthritis. (9th June 2015) - Riancho, L.; Corrales, A.; Santos-Gόmez, M.; Rueda-Gotor, J.; Blanco, R.; González-Gay, M.A.
Abstract : Background: Patients with rheumatoid arthritis have an increased risk of cardiovascular disease. Objectives: To evaluate the influence of the classic cardiovascular risk factors in the development of premature atherosclerosis. Methods: A set of 592 consecutive RA patients from a single university hospital without history of cardiovascular (CV) events were studied. Both traditional cardiovascular risk factors and the Systematic Coronary Risk Evaluation (SCORE) modified according to the EULAR recommendations (mSCORE) were assessed. Carotid ultrasonography was performed in patients and controls by a MyLab 70 scanner (Esaote; Genoa, Italy), equipped with 7–12 MHz linear transducer and the automated software guided technique radiofrequency – Quality Intima Media Thickness in real - time ( QIMT, Esaote, Maastricht, Holland ) to determine carotid intima-media thickness (cIMT) and plaques, according to Mannheim consensus. After the univariate analysis, multivariate regression models were fitted to adjust for potential confounders. Results: 592 patients (456 women, 136 men) with a mean age of 59±13 years were studied. Among them, 85% presented at least one classic cardiovascular risk factor; dyslipidemia (DLP) (43%), hypertension (HT) (42%), tobacco use (26%), hypertriglyceridemia (16%), diabetes mellitus (DM) (10%) and chronic kidney disease (CKD) (3%). In the univariate analysis, the cIMT was significantly associated with age, sex, DLP, HTA, DM, CKD and hypertriglyceridemia. Carotid plaques were associated with age, as well as with DLP, HTA and DM. A positive correlation between the mSCORE and cIMT was found (r=0, 50; p<0.001). The frequency of carotid plaques among patients classified as mild, moderate, and high CV risk according to mSCORE was 25%, 67% and 86%, respectively (p<0, 001). In the multivariate analysis, factors that were independently associated with cIMT were the age, male sex, DM, and smoking (p<0.002 in all cases). Carotid plaques were significantly associated with age and tobacco use (TABLE ). Conclusions: Our study demonstrates a close relationship between carotid ultrasonography findings (plaques and increased cIMT) and classic CV risk factors in RA patients. This could explain, at least partially, the increased risk of CV disease in these patients. Disclosure of Interest: None declared